The education sector in Mozambique: From access to epistemic quality in primary education - Mouzinho Mário; Celso Marcos Monjane; Ricardo Santos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
From the early days of national independence in 1975, the central aim of the educational policy in Mozambique has been to ensure that all school-age children have access to school and can remain there until they have completed their basic education. In the pursuit of this aim, the extension of access to primary education was achieved relatively successfully, given that it reached a net rate of school coverage of almost 100 per cent. However, the impressive increase in school attendance rates has not been accompanied by a corresponding improvement in the quality of learning, and there are worrying signs of a considerable setback in relation to this aspect. Using this observation as a starting point, the study identifies and analyses the variables in the institutional context behind 'schooling without learning'. The results of the study point to (i) weak state capacity; (ii) excessive dependence on external aid; and (iii) poor community involvement and participation in school management, as being factors with a major influence on the poor quality of education in primary schools.
Keywords: H11; H75; I21; 330; state capacity; dependence; education; participation; quality of education